(untitled) (Fiep Bulletin - online, 2016)
Diabetes Mellitus (DM) is a disease whose deficit absence of insulin secretion, this disease may present alterations in the sensitivity of the hands that may result in loss of grip strength (FPM), affecting the realization of life activities daily (ADL’S). Thus the aim of this study was to evaluate the influence of diabetes mellitus in sensitivity and grip strength. 25 diabetic females were evaluated. The sensitivity was evaluated by the Weinstein Monofilament Semmens-. The handgrip strength was assessed using the JAMAR ® dynamometer. The results showed loss of sensitivity of the ulnar nerve with 67%, and 76% of the median nerve. FPM in 56% of evaluated had disabilities. In the correlation between the loss of sensitivity and FPM Data reported a moderate correlation between the median nerve (Pearson r = 0.62) and the ulnar nerve (Pearson r = 0.49) which is . Concludes Diabetes Mellitus affects the sensitivity and grip strength.